2022
DOI: 10.1007/s00404-022-06672-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth (IVG) of human ovarian follicles in frozen thawed ovarian cortex tissue culture supplemented with follicular fluid under hypoxic conditions

Abstract: Background Despite its clinical success rates, transplantation after ovarian tissue cryopreservation (OTC) remains a matter of concern. Certain cancer subtypes may lead to the transfer of malignant cells when transplantation of affected ovarian tissue is conducted. IVG and subsequent isolation of vital follicles obtained from frozen thawed ovarian tissue for further in vitro maturation (IVM) would expand current fertility protection techniques while reducing the risk of retransplanting malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…In recent years, numerous studies have explored various culture conditions aimed at fostering follicle growth in vitro , predominantly relying on ovarian tissue culture ( Laronda et al , 2014 ; Xiao et al , 2015 ; Younis et al , 2017 ; Schallmoser et al , 2022 ). The achievement of our study is the demonstrated development of human ovarian primordial/intermediate follicles into secondary follicles within a remarkably short span of one week in a three-dimensional in vitro co-culture setting.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have explored various culture conditions aimed at fostering follicle growth in vitro , predominantly relying on ovarian tissue culture ( Laronda et al , 2014 ; Xiao et al , 2015 ; Younis et al , 2017 ; Schallmoser et al , 2022 ). The achievement of our study is the demonstrated development of human ovarian primordial/intermediate follicles into secondary follicles within a remarkably short span of one week in a three-dimensional in vitro co-culture setting.…”
Section: Discussionmentioning
confidence: 99%
“…One major key aspect to assess the quality of ovarian cortex tissue is follicular viability that can be evaluated with calcein, a well-described fluorescence-based live assay [42][43][44]. The incubation period of 24 h prior viability measurements of fresh, slow frozen/thawed and vitrified/rapid warmed tissue enables the tissue to express potential damage that could potentially occur with these procedures and may potentially not be observed when analyzed at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…Cortex samples were slow frozen and thawed according to published protocols with modifications 21 26 . In brief, tissue was equilibrated in L-15 Leibovitz’s medium (Gibco Life technologies, NY, U.S.A.) supplemented with 11% human serum albumin [HSA] (Irvine Scientific, Santa Ana, USA), 10% dimethyl sulfoxide [DMSO] (CryoSure DMSO, WAK Chemie, Steinbach, Germany) for 40 min prior to slow freezing procedure at a cooling rate of − 2 °C per min.…”
Section: Methodsmentioning
confidence: 99%